JB Soedirman Airport Sustainability Strategy to Encourage Regional Economic Strengthening - Abdul Aziz Ahmad; Pahrul Fauzi; Khalid Eltayeb Elfaki; Taqiuddin Fadhillah Ahmad (EKO-REGIONAL, 2023)
In the age of contemporary transportation, aviation is a significant subject. Developing nations or areas will increasingly need effective transportation. Significant economic developments are anticipated to benefit areas with airport infrastructure. This research discusses the responses of the community, including those of government officials and entrepreneurs, in Purbalingga Regency regarding the existence of Sudirman Airport which has been developed as a commercial airport and has been operating since 2021. In Purbalingga Regency, where Jenderal Besar Soedirman (JB Soedirman) Airport is located, this study seeks to understand how significant local communities believes the airport is to the region's ability to advance economically. The comprehensive interviewing of chosen respondents used in this study gives it a qualitative aspect. The findings of the study demonstrate that the presence of JB Soedirman Airport offers promising prospects for local development. The airport's presence indicates the potential for investment growth and business capitalization in Purbalingga Regency. The Purbalingga Regency government must provide the appropriate policy formulation to support the continuity and sustainability of the airport's operations in order to take advantage of the numerous favorable chances